Gaps and Overlaps in Supervisory Responsibilities: A Case Study of Bachelor’s and Master’s Students’ Thesis Writing in Two Departments - Olsson, Ulf; Hallberg, David (Journal of Academic Writing, 2018)
This article focuses on how supervisors and students perceive their responsibilities at the beginning of the thesis writing process. Students in general do little research writing before beginning their Bachelor’s or Master’s programs and they often find academic writing to be a complicated task, which means that many do not complete their thesis writing within the stipulated time. A survey was conducted at the Department of Computer and Systems Sciences (DSV) and the Department of Child and Youth Studies (BUV) at Stockholm University, Sweden. In addition to the distribution of responsibility, participants ranked the importance of four issues: the student’s own collected data in the thesis; language, layout, and correct referencing; the thesis as an excellent product; and the student’s development of his or her competence. In general, students and supervisors agreed on the distribution of responsibilities between them and the importance of some of the issues. The opinions were coherent, considering the survey was conducted early in the thesis writing period. It is suggested that future research includes an in-depth investigation of cultural differences between departments.